The Effect Of Problem Solving Method On Students' Learning Outcomes In History Subject In Grade X Of SMA Negeri 1 Mendo Barat Bangka - Rika Damayanti; Sani Safitri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2018)
This thesis is entitled the influence of the Problem Solving method on student learning outcomes in historical subjects in class X of SMA Negeri 1 Mendo Barat Bangka. The formulation of the problem in this study is how the effect of the Problem Solving method on student learning outcomes in History subjects in SMA 1 Mendo Barat Bangka. This study uses an experimental method that is treatment and without treatment. The population in this study were all class X which amounted to 171 students, while the study sample was taken by Random Sampling technique so that it was obtained as a sample of 74 students namely the experimental class (class X IPA 1) totaling 37 students and the control class (class X IPA 2) amounting to 37 students. Data collection was carried out through the implementation of both pree test and post test which numbered 25 multiple choice questions. The results of this study indicate that, in the experimental class, the average learning outcomes of the final test students were 79.43, while the control class average student learning outcomes obtained in the final test was 68.86. Furthermore, the data were analyzed using the t test with a significant level of α = 0.05 and dk = n1 + n2 - 2 = 72 which is 1.66, obtained by the hypothesis test t count of 4.76 because t count> t table (4.76> 1.66) then accept Ha and reject Ho, meaning learning history by applying the Problem Solving method gives an influence on student learning outcomes in class X SMA 1 Mendo Barat Bangka.